Nutrigenomics and immune function in fish: new insights from omics technologies. (October 2017) - Martin, Samuel A.M.; Król, Elżbieta
Abstract: The interplay between nutrition and immune system is well recognised, however the true integration of research between nutrition, animal energy status and immune function is still far from clear. In fish nutrition, especially for species maintained in aquaculture, formulated feeds are significantly different from the natural diet with recent changes in nutrient sources, especially with protein and oil sources now being predominated by terrestrial derived ingredients. Additionally, many feeds are now incorporated to health management and termed functional feeds, which are believed to improve fish health, reduce disease outbreaks and/or improve post-infection recovery. Using new omics technologies, including transcriptomics (microarray and RNA-seq) and proteomics, the impacts of nutrition on the immune system is becoming clearer. By using molecular pathway enrichment analysis, modules of genes can indicate how both local (intestinal) and systemic immune function are being altered. Although great progress has been made to define the changes in host immune function, understanding the interplay between fish nutrition, intestinal microbiome and immune system is only just beginning to emerge. Highlights: Nutrition has direct impacts on fish health and immunity. Omics technologies are essential for understanding diet and immunity interactions. Omics approaches help to improve functionality and sustainability of aquaculture feeds. Future research should focus on microbiota, early life experience and adaptive immunity.